In vitro and in planta testing of microbial agents for dual biological control of granary weevil and storage fungi on stored wheat grain - Gülçin Ercan; Anthony O. Adesemoye; Gary Y. Yuen; Sydney Everhart; James F. Campbell; Julie A. Peterson (Biological Control)
The granary weevil Sitophilus granarius is a serious pest that causes large economic losses to stored cereals. Similarly, storage fungi in the genera Aspergillus, Fusarium, and Penicillium can infest stored grain, causing deterioration of grain quality and contamination with mycotoxins that threaten animal and human health. The impact of these pests is magnified when they co-occur. Current management includes chemical pesticides and the manipulation of storage conditions, but undesirable pesticide residues, evolution of resistance, and practical and economic limitations may reduce their effectiveness and adoption. The aim of this study was to identify biological control agents (BCAs) that show dual effects against both granary weevil and three important storage fungi in stored grain. In vitro and in planta bioassays tested the effects of five bacterial and ten fungal strains of BCAs on granary weevil and three storage fungi: Aspergillus parasiticus, Fusarium graminearum, and Penicillium chrysogenum. The in vitro bioassays challenged storage fungi or weevils directly with BCAs in Petri plates while the in planta bioassays subjected pests to wheat seeds treated with BCAs. All BCAs exhibited some inhibitory effects against all pests, although Trichoderma gamsii (strains E1032 and E1064) and Bacillus amyloliquefaciens C415 were the most effective in causing mortality of granary weevil and suppressing growth of storage fungi. Metarhizium anisopliae E213 and Bacillus thuringiensis C423 showed strong sublethal effects on granary weevil by reducing oviposition and feeding damage. These studies reveal the potential for dual biological control of critical insect and storage fungi pests in stored cereal grains.